2017
DOI: 10.1080/08923973.2017.1284230
|View full text |Cite
|
Sign up to set email alerts
|

Pramipexole reduces inflammation in the experimental animal models of inflammation

Abstract: Pramipexole is a dopamine (DA) agonist (D2 subfamily receptors) that widely use in the treatment of Parkinson's diseases. Some epidemiological and genetic studies propose a role of inflammation in the pathophysiology of Parkinson's disease. To our knowledge, there is no study regarding the anti-inflammatory activity of pramipexol. Therefore, the aim of the study was to investigate anti-inflammatory effect of pramipexol. Anti-inflammatory effects of pramipexole were studied in three well-characterized animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Ear edema caused by croton oil or its irritant principle 12-O-tetradecanoylphorbol-13-acetate (TPA) has been extensively used to assess the anti-inflammatory activity of steroidal and non-steroidal anti-inflammatory drugs [132]. TPA-induced ear inflammation represents the model of skin inflammation useful for the appraisal of systemic and local anti-inflammatory compounds [135]. Topical administration of croton oil causes vasodilatation, promote vascular permeability, neutrophil influx, synthesis of eicosanoids, and liberation of serotonin and histamine [130].…”
Section: Anti-inflammatory Drug Development From Natural Products:mentioning
confidence: 99%
“…Ear edema caused by croton oil or its irritant principle 12-O-tetradecanoylphorbol-13-acetate (TPA) has been extensively used to assess the anti-inflammatory activity of steroidal and non-steroidal anti-inflammatory drugs [132]. TPA-induced ear inflammation represents the model of skin inflammation useful for the appraisal of systemic and local anti-inflammatory compounds [135]. Topical administration of croton oil causes vasodilatation, promote vascular permeability, neutrophil influx, synthesis of eicosanoids, and liberation of serotonin and histamine [130].…”
Section: Anti-inflammatory Drug Development From Natural Products:mentioning
confidence: 99%
“…The US Food and Drug Administration (FDA) has approved it as a drug used for the treatment of Parkinson's disease and restless leg syndrome ( Pich and Collo, 2015 ; Benbir and Guilleminault, 2006 ). It is reported that PPX exerts neuroprotective effects by reducing oxidative damage, mitochondrial dysfunction and apoptosis, owing to its role as an inhibitor or scavenger of free radicals, and blocks mitochondrial permeability transition pores (mtPTPs) through the inhibition of depolarizing membrane currents in dysfunctional mitochondria in various models ( Inden et al, 2009 ; Sayeed et al, 2006 ; Sadeghi et al, 2017 ). PPX inhibits the early brain injury after subarachnoid hemorrhage ( Ma et al, 2016 ) and significantly reduces lipid peroxidation in a rat model of Parkinson's disease ( Zou et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine D2 receptor (Drd2) has been regarded as a potential anti-inflammatory target in the therapy of NDDs [ 19 21 ]. Drd2 expresses both in neurons and astrocytes [ 22 ].…”
Section: Introductionmentioning
confidence: 99%